Improving Socio-Emotional Skilss Through Project Method in Islamic Elementary School Student - Hanah, Anah Siti; Nurdiansyah, Rikrik (Department of Teacher Professional Education, Tarbiya and Teacher Training Faculty, UIN Sunan Gunung Djati Bandung, 2024)
The purpose of this study is to improve the social emotional of group B children at RA Alkhoeriyah Rajadesa, Ciamis Regency through watermelon seed planting activities using the project method. The project method is one way that can be used in teaching to train children's ability to solve problems in everyday life and can move children to work together with other children where each part of the work is individual or in small groups to achieve shared goals. The research method in this article uses the classroom action research method with the research subjects being teachers and students of group B RA Alkhoeriyah consisting of 12 children, 4 boys and 5 girls. From the data on melon seed planting activities in cycle I, it was found that 6 students or 50.00% of the total children in group B received the MB category, 4 students or 33.34% of the total children in group B received the BSH category, while there were still 2 children receiving the BB category. Meanwhile, from the data of cycle II actions, it was found that 4 children or 33.34% of the total children in the class received the BSB category, 6 children or 50.00% of the total children in the class received the BSH category, while 2 students received the MB category, with a percentage value of 16.67%.